Pemahaman Keberagaman Peserta Didik Berdasarkan Profil Peserta Didik Sebagai Upaya Pemenuhan Target Kurikulum Merdeka - Tri Kurniawati; Nadia Ayu Rifani Putri (Jurnal Ecogen, 2023)
The purpose of this study is to provide an understanding of the diversity of students in terms of learning styles and student profiles to fulfill the targets of the Kurikulum Merdeka. The research method used is descriptive quantitative research with a one-way ANOVA analysis. The object of this research is the X.E.5 students at SMAN 2 Padang. The teacher's understanding of learning styles and student profiles is expected to be able to assist teachers in determining appropriate learning strategies and methods so that Kurikulum Merdeka's targets can be achieved. The results show that: 1) Gender differences do not have a significant effect on student learning outcomes; 2) Differences in the work of parents do not influence student learning outcomes; and 3) Differences in learning styles affect student learning outcomes.